Relations between human leukocyte antigens and autoimmune hepatitis in Turkish children - Seda GEYLANİ GÜLEÇ and Nafiye URGANCI and Tuğçin Bora POLAT and Emirzad DEMİREL and Erkan YILMAZ (Turkish Journal of Gastroenterology, 2019)
-